Digital Competency-Based Recruitment and MSME Human Resource Performance: The Role of Person–Job Fit and Task Complexity - Marthin, Romawi; Gambir, Jurianto; Wijaya, Andrianus; Chistina Iman Kalis, Maria (Jurnal Ilmiah Sumber Daya Manusia, 2026)
The rapid advancement of digital technologies has reshaped human resource management practices in micro, small, and medium enterprises (MSMEs). This study examines the effect of digital recruitment on human resource performance, with particular attention to the mediating role of person–job fit and the moderating role of task complexity. A quantitative survey method was applied to 30 MSMEs that have implemented digital recruitment systems. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess the causal relationships among the proposed variables. The findings reveal that digital recruitment has a significant positive effect on both human resource performance and person–job fit. Moreover, person–job fit significantly mediates the relationship between digital recruitment and performance outcomes. Task complexity is also found to moderate the relationship between digital recruitment and person–job fit, indicating the growing importance of digital competencies in highly complex work contexts. Overall, the results highlight the strategic importance of integrating digital recruitment practices, competency alignment, and task adaptability to enhance human resource performance in MSMEs within the digital era.